2016
DOI: 10.7205/milmed-d-15-00258
|View full text |Cite
|
Sign up to set email alerts
|

Patients Provide Recommendations for Improving Patient Satisfaction

Abstract: National Committee for Quality Assurance recommends patient-centered medical homes incorporate input from patient populations; however, many health care organizations do not. This qualitative study used two open-ended questions from 148 active duty Army Soldiers and their family members to illicit recommendations for primary care providers and clinic leadership that would improve their health care experiences. Content analysis and descriptive statistics were used to analyze responses. Participant responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Other studies found that reduced time spent with a physician combined with increased waiting time coincided with notable drops in patient satisfaction (Camacho, Anderson, Safrit, Jones, & Hoffmann, ). More recently, several studies have highlighted the increasingly important roles of spending more time, not feeling rushed, and offering genuine care—that is, displays of concern and care characteristic of interpersonal quality—and that waiting time was not as important (Long et al, ; Merlino, ; Moore, Hamilton, Krusel, Moore, & Pierre‐Louis, ). Putting patients first through improved interpersonal quality of care was also echoed as the most important driver for improving patient satisfaction, even by the President and Chief Transformation Officer of Press Ganey (Merlino & Raman, ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Other studies found that reduced time spent with a physician combined with increased waiting time coincided with notable drops in patient satisfaction (Camacho, Anderson, Safrit, Jones, & Hoffmann, ). More recently, several studies have highlighted the increasingly important roles of spending more time, not feeling rushed, and offering genuine care—that is, displays of concern and care characteristic of interpersonal quality—and that waiting time was not as important (Long et al, ; Merlino, ; Moore, Hamilton, Krusel, Moore, & Pierre‐Louis, ). Putting patients first through improved interpersonal quality of care was also echoed as the most important driver for improving patient satisfaction, even by the President and Chief Transformation Officer of Press Ganey (Merlino & Raman, ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…But with chronic diseases now being the primary health crisis, a new approach is needed that involves the individual receiving care, and his/her family, as primary stakeholders. 20,32,115,127 The individual ultimately has to be part of the preventive and predictive approach in order to be successful. 62 Involving the individual in personalized treatment and preventive interventions and improved data collection through self-tracking will be important factors.…”
Section: Participatory 20mentioning
confidence: 99%
“…13 Multiple previous national polls have identified lengthy waits as the most commonly identified serious problem facing the Canadian health care system, with one recent survey finding that 94% of Canadians are either concerned or somewhat concerned about wait times to see a specialist. 14,15 Furthermore, previous studies have shown waiting time to be a significant contributor to patient satisfaction, 16 and a 2014 poll found that 47% of Canadians were dissatisfied with wait times. 15 In our study, the use of eConsult prevented an unnecessary referral in 48.7% of cases where the PCP had initially planned a formal consultation.…”
Section: Reducing Wait Timesmentioning
confidence: 98%